2006
DOI: 10.1146/annurev.ento.51.110104.151120
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Competition, Quantitative Food Webs, and the Structure of Phytophagous Insect Communities

Abstract: Phytophagous insects and their natural enemies make up one of the largest and most diverse groups of organisms on earth. Ecological processes, in particular negative indirect effects mediated by shared natural enemies (apparent competition), may be important in structuring phytophagous insect communities. The potential for indirect interactions can be assessed by analyzing the trophic structure of insect communities, and we claim that quantitative food webs are particularly well suited for this task. We review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
203
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(206 citation statements)
references
References 136 publications
1
203
0
2
Order By: Relevance
“…We focused on quantitative metrics that reflect interaction network properties and that are more robust against variation in sampling intensity, matrix size, and symmetry than qualitative ones (van Veen et al., 2006). Specifically, we used: (a) number of compartments (subsets of the web not connected to other compartments); (b) weighted nestedness based on overlap and decreasing fill (nestedness quantifies whether a given sequence of columns [rows] shows decreasing marginal totals, that is, incidences or richness); (c) weighted quantitative linkage density (linkage density is the weighted diversity of interactions per species); (d) weighted quantitative connectance (connectance is the weighted realized proportion of possible links, calculated as quantitative linkage density divided by the number of species in the network); (e) weighted quantitative interaction evenness (interaction evenness is a measure of the uniformity of energy flows along different pathways); (f) weighted quantitative network specialization index H2 (degree of specialization among hosts and parasitoids across an entire network); (g) weighted quantitative generality (generality is the mean effective number of hosts per parasitoid weighted by their marginal totals); (h) weighted quantitative vulnerability (vulnerability is the mean effective number of parasitoids per host species, weighted by their marginal totals); and (i) weighted quantitative modularity (modularity is the degree to which a quantitative network can be divided into modules, within which within‐module interactions are more prevalent than between‐module interactions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on quantitative metrics that reflect interaction network properties and that are more robust against variation in sampling intensity, matrix size, and symmetry than qualitative ones (van Veen et al., 2006). Specifically, we used: (a) number of compartments (subsets of the web not connected to other compartments); (b) weighted nestedness based on overlap and decreasing fill (nestedness quantifies whether a given sequence of columns [rows] shows decreasing marginal totals, that is, incidences or richness); (c) weighted quantitative linkage density (linkage density is the weighted diversity of interactions per species); (d) weighted quantitative connectance (connectance is the weighted realized proportion of possible links, calculated as quantitative linkage density divided by the number of species in the network); (e) weighted quantitative interaction evenness (interaction evenness is a measure of the uniformity of energy flows along different pathways); (f) weighted quantitative network specialization index H2 (degree of specialization among hosts and parasitoids across an entire network); (g) weighted quantitative generality (generality is the mean effective number of hosts per parasitoid weighted by their marginal totals); (h) weighted quantitative vulnerability (vulnerability is the mean effective number of parasitoids per host species, weighted by their marginal totals); and (i) weighted quantitative modularity (modularity is the degree to which a quantitative network can be divided into modules, within which within‐module interactions are more prevalent than between‐module interactions).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there has been a shift from simply documenting the incidence of interactions among herbivores and their parasitoids toward establishing quantitative food webs, which provide further insights into the processes shaping herbivorous insect communities and their structure (Memmott & Godfray, 1994; van Veen, Morris, & Godfray, 2006). However, only three studies have investigated the vertical stratification of host–parasitoid food webs (Chaij, Devoto, Oleiro, Chaneton, & Mazía, 2016; Morris et al., 2015; Paniagua, Medianero, & Lewis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Species interactions through the sharing of predators could be either positive or negative (Abrams and Matsuda, 1996), although effects of trait-mediated interactions (Peckarsky et al, 2008;Preisser and Bolnick, 2008) will often be negative. It has been suggested that apparent competition is quite common in large and diverse groups of organisms, such as phytophagous insects (van Veen et al, 2006).…”
Section: Beyond Idealized Resource Competitionmentioning
confidence: 99%
“…2006). Interspecific competition for floral resources may result in the exploitation of food resources by the stronger competitor and a reduced food supply for the weaker competitor.…”
Section: Introductionmentioning
confidence: 99%